DEVELOPMENT OF A CLUSTER MODULE OF ORGANIZING PHYSICAL EDUCATION LESSONS WITH VISUALLY IMPAIRED AND BLIND STUDENTS - Тaniberdiyev Akmal Abdug‘aniyevich (Journal of Higher Education and Academic Advancement, 2024)
This article talks about the effectiveness of organizing physical education classes with blind and visually impaired students in a cluster module. The features of physical education and sports training in the physical and functional development of the body of visually impaired and blind students have been identified